Telecommunications, productivity and regional dependence: A comparative analysis between the Brazil, China and main developed regions in the post-reform period - Admir Antonio Betarelli Junior; Weslem Rodrigues Faria; Rosa Lívia Gonçalves Montenegro; Fernando Salgueiro Perobelli; Luiz Carlos de Santana Ribeiro (Journal of Economic Structures, 2022)
In the last two decades, new technologies and the rapid growth of the telecommunications sector have changed production and trade relations in world economic systems. Regional dependence on the level of productivity, supply and demand of telecommunications has increased worldwide. Our study analyzes the changes in total factor productivity (TFP) of telecommunications and verifies its global and regional importance between 2000 and 2014. We apply the TFP decomposition and extraction technique in an input-output model. The main findings suggest improved efficiency has resulted in TFP gains in developed countries, whose variations were lower than those of Brazilian telecommunications, which exhibit a low capital-labor ratio. Moreover, global and regional dependence is more sensitive to supply than the demand for telecommunications. Although the main effects on the regional output are intraregional, the backward and forward effects denote a heavy regional reliance on USA telecommunications and reciprocity between China and European countries. The increase in telecommunications influenced by national policies in countries with little emphasis on regional composition should generate minor marginal gains in TFP, even with the gain in productive efficiency. These policies are also expected to reduce the dependence on American and Chinese telecommunications.
Keywords: 330; Input-output model; Productivity; Regional dependency; Telecommunications